Komunikasi Persuasif Berbasis AI: Strategi Retorika Chatbot dalam Adopsi Bitcoin oleh Mahasiswa - Tjahyana, Lady Joanne (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2025)
This study aims to analyze how rhetorical strategies—ethos, logos, and pathos—are applied in an AI chatbot to educate university students about Bitcoin and encourage its adoption wisely. The AI chatbot was developed using the Chatfuel platform and integrated with WhatsApp as the primary communication medium. In this study, the AI chatbot was tested on 117 students from Petra Christian University with basic knowledge of AI. The researcher evaluated the AI chatbot effectiveness through qualitative content analysis and a survey. The results indicate that the AI chatbot adjusts its communication approach based on user characteristics and question types. The ethos strategy was effective in building trust, while logos was preferred for providing logical clarity, particularly for technical and investment-related questions. Pathos was used to evoke emotional awareness regarding Bitcoin's risks. Gender-based analysis showed that female students responded more to ethos and pathos, whereas male students were more inclined toward logos. Additionally, the chatbot utilized logos for basic knowledge questions, pathos and logos for risk-related inquiries, and a combination of ethos and logos for security and investment-related questions.These findings confirm that AI chatbots can enhance students' financial literacy by effectively adapting their communication strategies. This study contributes to the understanding of AI-driven communication in financial education and opens opportunities for developing more personalized and interactive AI chatbots in the future. ABSTRAK Penelitian ini bertujuan untuk menganalisis bagaimana strategi retorika ethos, logos, dan pathos diterapkan dalam chatbot AI untuk mengedukasi mahasiswa mengenai Bitcoin serta mendorong adopsinya secara bijak. Chatbot AI dikembangkan menggunakan platform Chatfuel dan diintegrasikan dengan WhatsApp sebagai media komunikasi utama. Dalam penelitian ini, chatbot AI diuji pada 117 mahasiswa Universitas Kristen Petra yang memiliki keahlian penggunaan AI , dan kemudian peneliti mengevaluasi efektivitas chatbot AI melalui analisis isi kualitatif dan survei. Hasil penelitian menunjukkan bahwa chatbot AI menyesuaikan pendekatan komunikasinya berdasarkan karakteristik pengguna dan jenis pertanyaan. Strategi ethos terbukti efektif dalam membangun kepercayaan, sementara logos lebih dihargai dalam memberikan kejelasan logis, terutama untuk pertanyaan teknis dan investasi. Pathos digunakan untuk membangkitkan kesadaran emosional terkait risiko Bitcoin. Analisis berbasis gender menunjukkan bahwa mahasiswa perempuan lebih merespons ethos dan pathos, sedangkan mahasiswa laki-laki lebih cenderung merespons logos. Selain itu, chatbot menggunakan logos untuk pertanyaan dasar, pathos dan logos untuk pertanyaan risiko, serta kombinasi ethos dan logos untuk pertanyaan tentang keamanan dan investasi.Temuan ini menegaskan bahwa chatbot AI dapat meningkatkan literasi keuangan mahasiswa dengan menyesuaikan strategi komunikasinya secara efektif. Penelitian ini memberikan kontribusi terhadap pemahaman tentang komunikasi berbasis AI dalam pendidikan keuangan dan membuka peluang untuk pengembangan chatbot yang lebih personal dan interaktif di masa depan.